2005
DOI: 10.1354/vp.42-3-282
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Mast Cells and Immunoglobulin-E Antibody Responses During Clearance ofTritrichomonas foetus

Abstract: Abstract. We showed earlier that Tritrichomonas foetus-specific bovine immunoglobulin (Ig)G1 and IgA antibodies in uterine and vaginal secretions are correlated with clearance of this sexually transmitted infection. Eosinophils have been noted in previous studies of bovine trichomoniasis but the role of mast cells and IgE responses have not been reported. The hypothesis that IgE and mast cell degranulation play a role in clearance was tested in 25 virgin heifers inseminated experimentally and infected intravag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 42 publications
1
7
0
1
Order By: Relevance
“…Immunostaining of parallel sections with mAb to TF1.17 antigen indicated uptake of antigen by epithelial cells and large MΦ or DC under the basement membrane near the lymphoid follicles (Rhyan et al, 1999). Similar antigen uptake has been detected in the infected female uterine and vaginal mucosa (Corbeil et al, 2005). Thus, even though the parasite is noninvasive, released TF1.17 antigen appears to be taken up by epithelial cells.…”
Section: Trichomoniasissupporting
confidence: 52%
See 1 more Smart Citation
“…Immunostaining of parallel sections with mAb to TF1.17 antigen indicated uptake of antigen by epithelial cells and large MΦ or DC under the basement membrane near the lymphoid follicles (Rhyan et al, 1999). Similar antigen uptake has been detected in the infected female uterine and vaginal mucosa (Corbeil et al, 2005). Thus, even though the parasite is noninvasive, released TF1.17 antigen appears to be taken up by epithelial cells.…”
Section: Trichomoniasissupporting
confidence: 52%
“…Parsonson et al (1976) showed that significant inflammation accompanied by reproductive failure did not occur until after 7 weeks of infection, so the vaccine should protect against fetal loss. Analysis of vaccine-induced antibody responses demonstrated predominantly IgG1 responses in the serum and IgA plus IgG1 antibodies in secretions (Corbeil et al, , 2005. IgE antibodies were also increased during infection.…”
Section: Trichomoniasismentioning
confidence: 98%
“…Experimental infection of female cattle with T. foetus (strain D1) can be detected by vaginal cultures for many weeks or months. 4,10,28 Because comparative data on experimental infection with T. vaginalis in humans are not available, it is possible that T. vaginalis infection of the even the natural host is less persistent than that of T. foetus . Pretreatment of mice with steroids and sex hormones was critical for achieving robust and extended vaginal infections with T. vaginalis.…”
Section: Discussionmentioning
confidence: 99%
“…Their prominence in T. foetus infection in cattle has been noted in several studies. 1,5,16,18,46 Their tissue damaging granules can have bystander effects on local tissues and marked vascular effects that lead to edema, although a specific role of eosinophils in trichomoniasis has not been determined. 26 However, their vascular effects could well contribute to the transport of antibodies to the uterine and vaginal lumen, and provide some protection from infection and later clearance of trichomonads.…”
Section: Discussionmentioning
confidence: 99%
“…58 This strain, at a dose of 1 3 10 6 T. foetus organisms intravaginally instilled, was used in several studies to intravaginally infect 100% of experimental heifers at estrus. 10,16 Parasites were maintained in culture by using trypticase-yeast extract-maltose (TYM) medium that contained 10% fetal calf serum until inoculation. 22 A mouse-adapted strain of T. foetus (MuTF 52100V) was developed by first intravaginally infecting BALB/ cAnNCr mice with strain D1.…”
Section: Parasitesmentioning
confidence: 99%